Effect of low-frequency assisted ultrasonic on cryopreservation of L-02 hepatocyte cells - Li, Weijie; Yang, Xi; Bi, Wenyan; Song, Liyong; Liu, Baolin (Frontiers in Cell and Developmental Biology, 2025)
Developing bioartificial liver and hepatocyte transplantation technology causes increasing hepatocyte cell demand. Effective long-term hepatocyte cell preservation methods are necessary to promote. Progressive cooling is a key preservation technology for cell banks. However, the cell solution needs to be supercooled in a slow freezing process. The high degree of supercooling possibly induces uncontrollable intracellular ice formation. This work designs an ultrasonic ice-seeding system for L-02 hepatocyte cell preservation, reducing supercooling and improving cell survival rate. The effect of ultrasonic intensities on the hepatocyte’s survival rate was investigated and optimized. The results prove the calorimetric method can efficiently measure the ultrasonic intensity dissipated in the hepatocyte cell preservation solution. When the ultrasonic intensity is 0.0329 W/cm2 ∼ 0.4316 W/cm2, the hepatocyte survival rate is over 90%. There is no significant difference between experiment groups (p < 0.05) when the ultrasonic intensity is larger than 0.4316 W/cm2. The hepatocyte cell survival rate reduced significantly with the increase of ultrasonic intensity. The 7-day hepatic function indicator experiment results indicate that the ultrasonic ice seeding has the weakest impact on hepatocyte cells in the four groups. The secretion of urea, albumin and glucose proved that ultrasonic ice seeding technology does not affect cell secretion and has an enormous advantage in cryopreservation. It can be widely applied to cell freezing fields.